Faecal-wood biomass co-combustion and ash composition analysis - Somorin, Tosin; Kolios, Athanasios J.; Parker, Alison; McAdam, Ewan J.; Williams, Leon; Tyrrel, Sean (Elsevier, 2017)
Fuel blending is a widely used approach in biomass combustion, particularly for feedstocks with low calorific value and high moisture content. In on-site sanitation technologies, fuel blending is proposed as a pre-treatment requirement to reduce moisture levels and improve the physiochemical properties of raw faeces prior to drying. This study investigates the co-combustion performance of wood dust: raw human faeces blends at varying air-to-fuel ratios in a bench-scale combustor test rig. It concludes with ash composition analyses and discusses their potential application and related problems. The study shows that a 50:50 wood dust (WD): raw human faeces (FC) can reduce moisture levels in raw human faeces by ∼40% prior to drying. The minimum acceptable blend for treating moist faeces without prior drying at a combustion air flow rate of 14–18 L/min is 30:70 WD: FC. For self-sustained ignition and flame propagation, the minimum combustion temperature required for conversion of the fuel to ash is ∼400 °C. The most abundant elements in faecal ash are potassium and calcium, while elements such as nickel, aluminium and iron are in trace quantities. This suggests the potential use of faecal ash as a soil conditioner, but increases the tendency for fly ash formation and sintering problems.
Keywords: Faecal ash; Combustion; Fuel blending; Non-sewered sanitary systems; Nano-membrane toilet; Soil conditioner